RURAL WOMEN’S ACCESS TO VARIOUS SOURCES OF INFORMATION IN TEHSIL FAISALABAD - K.M. Chaudhry; S. Muhammad; A. Saghir; I. Ashraf (Journal of Animal and Plant Sciences, 2008)
Rural women play an integral role in agriculture. But they have to face a lot of problems. They have no access to modern sources of information. In order to estimate the information gap in the study area, the present study has been planned for the rural women of tehsil Faisalabad. Out of which two rural union councils were randomly selected, from each of the selected Union Council, 2 villages were selected randomly. With help of union council office the rural women involved in in agricultural activities was prepared. After making the list, 30 females from each village were selected through simple random sampling procedure. Thus for the present study a total of 120 respondents were selected. The data were collected with the help of pre-tested and validated interview schedule. The data thus collected were analyzed with the help of Statistical Package for Social Sciences (SPSS). The results show that there is a significant relation between age, education alongwith TV and radio. Rural women used to like information disseminated through such media.
Keywords: Rural women; access; sources of information